Growth, recruitment and life history parameters of fish in Andean reservoirs - Escobar Cardona, Jorge Luis (2025)
Introduction: The formation of new anthromes such as reservoirs and dams to generate energy for human consumption, provides new environmental scenarios that condition the survival of the pre-existing fish species in the modified system. Objective: To estimate some of the main population attributes in relation to growth and recruitment discussed in the context of the life histories of the species analyzed for a high-Andean river system. Methods: Based on the historical sequence (2005-2017) for the seven species with the highest numerical record and frequency distributions, a typical population parameter estimation analysis was employed following the Growth Model proposed by von Bertalanffy (MCvB) and empirical equations to the respective complementary parameters. Results: A total of 28 651 frequency lengths were analyzed, finding that those species with rapid growth and lower longevity prefer artificial lacustrine environments, species with opportunistic life history strategies (Astyanax microlepis and Roeboides dayi) and with a bimodal recruitment pattern, while species with intermediate growth were seasonal (Brycon henni y Hemibrycon caucanus), registered in tributaries to the reservoir, and in equilibrium (Andinoacara latifrons, Chaetostoma thomsoni and Coptodon rendalli) mainly associated with rivers, reservoirs, and streams or transitional environments to reservoirs. Conclusion: The analysis of information on the population dynamics and live history of fish coexisting in a reservoir and its surrounding environments suggests a spatial segregation of fish species in response to a possible selection of their biological traits and other bioecological characteristics that sustain their local populations.